Direct phasing of protein crystals with high solvent content. Issue 1 (11th December 2014) - He, Hongxing; Su, Wu‐Pei
<x xml:space="preserve">Abstract</x> An iterative transform method is proposed for solving the phase problem in protein crystallography. In each iteration, a weighted average electron‐density map is constructed to define an estimated protein mask. Solvent flattening is then imposed through the hybrid input–output algorithm [Fienup (1982). Appl. Opt.21, 2758–2769]. Starting from random initial phases, after thousands of iterations the mask evolves into the correct shape and the phases converge to the correct values with an average error of 30–40° for high‐resolution data for several protein crystals with high solvent content. With the use of non‐crystallographic symmetry, the method could potentially be extended to phase protein crystals with less than 50% solvent fraction. The new phasing algorithm can supplement and enhance the traditional refinement tools.